Observing Sea States - Ardhuin, Fabrice; Stopa, Justin E.; Chapron, Bertrand; Collard, Fabrice; Husson, Romain; Jensen, Robert E.; Johannessen, Johnny; Mouche, Alexis; Passaro, Marcello; Quartly, Graham D.; Swail, Val; Young, Ian (Frontiers in Marine Science, 2019)
Sea state information are needed for many applications, ranging from safety at sea and on the coast, for which real time data is essential, to planning and design needs for infrastructure that require long time series. The definition of the wave climate and its possible evolutions requires high resolution data, and knowledge on possible drift in the observing system. Sea states are also an important climate variable that enters in air-sea fluxes parameterizations. Finally, sea state patterns can reveal the intensity of storms and associated climate patterns at large scales, and the intensity of currents at small scales. A synthesis of user requirements leads to requests for spatial resolution at kilometer scales, and estimations of trends of a few centimeters per decade. Such requirements cannot be met by observations alone in the foreseeable future, and numerical wave models can be combined with in situ and remote sensing data to achieve the required resolution. As today's models are far from perfect, observations are critical in providing forcing data, namely winds, currents and ice, and validation data, in particular for frequency and direction information, and extreme wave heights. In situ and satellite observations are particularly critical for the correction and calibration of significant wave heights to ensure the stability of model time series. A number of developments are underway for extending the capabilities of satellites and in situ observing systems. These include the generalization of directional measurements, an easier exchange of moored buoy data, the measurement of waves on drifting buoys, the evolution of satellite altimeter technology, and the measurement of directional wave spectra from satellite radar instruments. For each of these observing systems, the stability of the data is a very important issue. The combination of the different data sources, including numerical models, can help better fulfill the needs of users.